How blockchain technology can monetize new music ventures: an examination of new business models. Issue 4 (6th July 2020) - Owen, Robyn; O'Dair, Marcus
Abstract : Purpose: This paper aims to examine how blockchain technology is disrupting business models for new venture finance. Design/methodology/approach: The role of blockchain technology in the evolution of new business models to monetize the creative economy is explored by means of a case study approach. The focus is on the recorded music industry, which is in the vanguard of new forms of intermediation and financialization. There is a particular focus on emerging artists. Findings: This paper provides novel case study insights and concludes by considering how further research can contribute to building a theory of technology-driven business models which apply to the development, on the one hand, of new forms of financial intermediaries, more correctly referred to as "infomediaries, " and on the other hand, to new forms of direct monetization by artists. Originality/value: This paper provides early insight into the emerging potential applications of blockchain technologies to streamline music industry business service models and improve finance streams for new artists. The findings have far-reaching implications across the creative sector.